Nephrotoxicity Induced by the R- and S-Enantiomers of N-(3,5-Dichlorophenyl)-2-hydroxysuccinimide (NDHS) and Their Sulfate Conjugates in Male Fischer 344 Rats - Rankin, Gary O. (2007)
The agricultural fungicide N-(3,5-dichlorophenyl)succinimide (NDPS) induces nephrotoxicity characterized as polyuric renal failure and mediated via metabolites arising from oxidation of the succinimide ring. Recent findings have suggested that the stereochemical nature of NDPS metabolites may be an important factor in NDPS metabolite-induced nephrotoxicity. The purpose of the present study was to determine the role of stereochemistry in the in vivo nephrotoxicity induced by R-(+)- and S-(-)-N-(3,5-dichlorophenyl)-2-hydroxysuccinimide (R- and S-NDHS) and the in vitro nephrotoxicity induced by their enantiomeric sulfate conjugates, R-(-)- and S-(+)-N-(3,5-dichlorophenyl)-2-hydroxysuccinimide-O-sulfate (R- and S-NSC). Male Fischer 344 rats (4 rats/group) were administered intraperitoneally (ip) an enantiomer of NDHS (0.05, 0.1 or 0.2 mmol/kg) or vehicle, and renal function monitored for 48 h. R-NDHS (0.1 or 0.2 mmol/kg) had little effect on renal function. In contrast, S-NDHS (0.1 mmol/kg) induced marked nephrotoxicity. The nephrotoxic potential of R- and S-NSC (0.5, 0.75 or 1.0 mM) was determined using freshly isolated rat renal cortical cells (IRCC, 3-4 × 10(6) cells/ml). Cytotoxicity was determined by measuring the release of lactate dehydrogenase (LDH) at the end of a 1 h incubation period. The LDH release observed in these studies was similar between R- and S-NSC. These results indicate that stereochemistry is an important factor for NDPS metabolite nephrotoxicity and that the role of stereochemistry, at least for NSC, occurs at extra-renal sites.